La psicología cubana y la salud de los trabajadores : entre el malestar y el bienestar - Jorge Juan Román Hernández (Universidade do Porto, 2019)
The paper aims at communicating the origin and evolution of the application of psychological science to the multidisciplinary field of occupational health in Cuba. Several factors are taken into account in this process : the social and socio-labor context, with a relatively extensive exposure, given the uniqueness of the Cuban social system. The trajectory of occupational health in the country and its current critical situation. The contributions of the professional practice of psychologists in work scenarios, which gave rise to occupational health psychology as a line of work in research, teaching and professional practice. It emphasizes the need to develop theoretical and methodological work in this area from a psychodynamic point of view, which takes subjectivity into account, for which the cultural historical approach of L. S. Vygotsky is proposed.